Pengaruh Komunikasi Kerja, Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan UKM Elha Baby - Anni Solikah (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research aims to determine the influence of work communication variables (X1), motivation (X2) and work environment (X3) on employee performance (Y) of UKM Elha Baby. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. The sample selection obtained was 35 respondents from UKM Elha Baby. This research data was obtained through questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The results of the research obtained the multiple linear regression equation Y= -4.381 + 0.331X1 + 0.238 + 0.298 Work motivation has a partially significant effect on performance, with a sig. 0.048 > 0.05. The work environment has a partially significant effect on performance, with the result being a sig. 0.005 > 0.05. The F test results obtained Fcount results of 34,203 > from Ftable 3.28 with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that Communication, Work Motivation and the Environment simultaneously have a significant effect on the Performance of UKM Elha Baby Employees.